Multi-ion synergistic electrochromic film layer structure and porthole for manned spacecraft

CN122902139APending Publication Date: 2026-10-13BEIJING INST OF SPACECRAFT SYST ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611390619.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

(2)、解决现有电致变色膜系在太空极端环境下长期性能衰减的问题,通过高可靠性封装与结构设计,大幅提升舷窗系统的空间环境适应性与在轨服役寿命

Benefits of technology

(1)、调光性能实现跨越式提升:本发明提出的多离子协同电致变色机制,突破了传统单一Li+体系的性能瓶颈,通过Li+实现毫秒级可见光快速调光,通过Na+实现秒级近红外波段高效隔热,可同时满足太空场景下宽光谱、大范围调光与高效隔热的双重需求;可见光透光率最低可达10%,近红外波段阻隔率最高可达92%,响应速度较传统体系提升一个数量级以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122902139A_ABST
    Figure CN122902139A_ABST
Patent Text Reader

Abstract

The present application relates to a multi-ion synergistic electrochromic film layer structure and a porthole for manned spacecraft, and belongs to the technical field of cross between intelligent materials and aerospace structure design. The multi-ion synergistic electrochromic film layer structure is a full-solid sandwich structure composite film system, which realizes wide-spectrum, fast-response light modulation and heat insulation performance through the synergistic effect of two active alkali metal ions with different radii. The multi-ion synergistic electrochromic film layer structure forms a standardized electrochromic sandwich preform through standardized preform packaging design and ALD full-wrapping barrier technology, and the electrochromic sandwich preform is integrally laminated to the inner surface of the non-load-bearing glass through optical-grade OCA glue to form an electrochromic porthole for manned spacecraft, which can effectively resist the erosion of extreme working conditions such as atomic oxygen, strong cosmic rays and high-low temperature cycles, and greatly improve the on-orbit service life and cycle stability of the film system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a multi-ion synergistic electrochromic film structure and porthole for manned spacecraft, belonging to the interdisciplinary field of smart materials and aerospace structural design. Specifically, it belongs to two major technical directions: electrochromic smart dimming materials and manned spacecraft porthole structure design. It is particularly suitable for the intelligent dimming and system integration design of ultra-large portholes in manned spacecraft, space stations and other on-orbit manned spacecraft. Background Technology

[0002] During their operation in orbit, manned spacecraft face an extreme and rapidly changing space lighting environment. Near-Earth orbit spacecraft complete a day-night cycle every 90 minutes. The direct sunlight, which is not filtered by the Earth's atmosphere, contains high-intensity ultraviolet, visible, and near-infrared radiation across the entire spectrum. This not only easily causes sunburn and visual glare for the occupants but also significantly increases the load on the cabin's thermal control system. Therefore, the windows of manned spacecraft must have a wide spectral range and a fast-response intelligent dimming capability.

[0003] Existing electrochromic color-changing lighting technology, used in aviation, shipbuilding, and other fields, suffers from numerous technical shortcomings when applied to the space environment, as detailed below: (1) The dimming performance has an inherent bottleneck: most of the existing mainstream electrochromic solutions use a single Li + The ion-driven WO3-based thin film system has reached the limit of material theory in terms of dimming performance. It cannot simultaneously meet the wide-spectrum synergistic adjustment requirements of wide-range dimming in the visible light band and efficient heat insulation in the near-infrared band in space scenarios. Moreover, it has slow response speed and poor color uniformity when used in large-size applications.

[0004] (2) Insufficient adaptability and durability to the space environment: The space environment contains extreme conditions such as strong cosmic rays, atomic oxygen, and high and low temperature cycles. Existing electrochromic film encapsulation solutions cannot effectively resist long-term space radiation and are prone to problems such as film performance degradation and failure, which cannot meet the requirements of long life and high reliability of manned spacecraft.

[0005] Based on the shortcomings of the existing technologies, there is an urgent need in this field to develop an overall solution for electrochromic portholes that has better dimming performance, stronger adaptability to the space environment, and can be deeply adapted to manned spacecraft. Summary of the Invention

[0006] The technical problem solved by this invention is to overcome the shortcomings of the prior art and provide a multi-ion synergistic electrochromic film structure and porthole for manned spacecraft, mainly solving the following technical problems: (1) Break through the performance bottleneck of single-ion electrochromic system, and achieve wide-spectrum, wide-range, fast-response dimming in visible and near-infrared bands through multi-ion synergistic mechanism, while taking into account high-efficiency heat insulation performance. (2) Solve the problem of long-term performance degradation of existing electrochromic film systems in the extreme environment of space. Through high-reliability packaging and structural design, significantly improve the space environment adaptability and on-orbit service life of the porthole system.

[0007] The solution of this invention is: a multi-ion synergistic electrochromic film structure, which includes a first electrode layer, an ion storage and catalytic layer, a solid mixed ion electrolyte layer, a main electrochromic layer, and a second electrode layer; wherein: The first electrode layer and the second electrode layer are transparent conductive oxide thin films. The first electrode layer is used as a cathode driving electrode, and the second electrode layer is used as an anode driving electrode. The ion storage and catalytic layer is a porous nanofilm containing interconnected nanopores within which two active ions, Li, are pre-embedded. + and Na + ; A solid-state hybrid ionic electrolyte layer comprises a polymer-based solid electrolyte matrix, within which NASICON-type fast ion conductor nanoclusters are dispersed; the solid electrolyte matrix is ​​used to realize Li + The NASICON-type fast ion conductor nanoclusters possess the ability to conduct Na+. + Selective conduction capability; The main electrochromic layer is a vertically grown WO3 nanorod array structure.

[0008] Preferably, the porosity of the ion storage and catalyst layer is ≥30%.

[0009] Preferably, in the solid mixed ionic electrolyte layer, the polymer-based solid electrolyte matrix is ​​a PEO-based polymer solid electrolyte, the doping amount of NASICON-type fast ion conductor nanoclusters is 8-15wt%, the nanocluster particle size is controlled at 50-100nm, and the thickness of the solid mixed ionic electrolyte layer is 1-3μm.

[0010] Preferably, in the main electrochromic layer, the porosity of the WO3 nanorod array structure is ≥40%, and the specific surface area is controlled in the range of 45~60 m² / g.

[0011] Preferably, the electrochromic lighting process of the multi-ion synergistic electrochromic film structure includes a coloring process and a fading process. The coloring process includes a first-order fast response stage and a second-order deep coloring stage, realizing Li + First embedding, Na + Post-embedded hierarchical collaborative control, wherein: First-order fast response stage: Applying a negative driving voltage to the multi-ion synergistic electrochromic film structure, Li ions with small ionic radii and fast migration rates... +First, the ion storage and catalytic layer is extracted and inserted into the WO3 lattice of the main electrochromic layer through the solid mixed ion electrolyte layer, triggering the electrochromic reaction of WO3 and achieving millisecond-level initial coloring. Second-order depth coloring stage: As the negative driving voltage is continuously applied, Na+ ions with large ionic radii and slow migration rates... + Through the selectively conductive channels of NASICON-type fast ion conductor nanoclusters, they are gradually embedded into the WO3 lattice of the main electrochromic layer, achieving second-level deep coloring on the basis of preliminary coloring.

[0012] Preferably, the negative driving voltage of the coloring process is determined by the following method: Calibration of the coloring voltage-visible transmittance function of multi-ion synergistic electrochromic film structure Coloring voltage-near-infrared blocking rate function ; Based on the target value of visible light transmittance Coloring voltage-visible light transmittance function Combined with the incident angle correction factor To obtain a separate driver for Li + The coloring voltage, denoted as ; In the formula , Li + Embedded threshold voltage, Li + Saturation embedding voltage; Based on the target value of near-infrared blocking rate Coloring voltage-near-infrared blocking rate function Combined with the ion-coordinated voltage coupling coefficient To obtain a separate driving Na + The coloring voltage, denoted as Ensure Na + In Li + Embedded functionality will be implemented after startup; In the formula , Na represents + Embedded threshold voltage, Na represents + Saturation embedding voltage; Pick and The larger value in the range is used as the negative driving voltage for the coloring process. .

[0013] Preferably, the fading process is as follows: when a positive driving voltage is applied to the multi-ion synergistic electrochromic film structure, Na... + and Li + The cells were successively de-intercalated from the main electrochromic layer and re-intercalated into the ion storage and catalytic layer, and the multi-ion synergistic electrochromic film structure completed the fading process.

[0014] Preferably, the forward driving voltage for the fading process is determined by the following method: Calibration of the fading voltage-near-infrared blocking rate function of multi-ion synergistic electrochromic film structure and fading voltage-visible light transmittance function ; Based on the target value of near-infrared blocking rate and fading voltage-near-infrared blocking rate function To obtain a separate driving Na + fading voltage ; In the formula , Na represents + De-intercalation threshold voltage Na represents + Complete de-intercalation saturation voltage; Based on the target value of visible light transmittance and fading voltage-visible light transmittance function To obtain a separate driver for Li + fading voltage ; In the formula , Li + De-intercalation threshold voltage Li + Complete de-intercalation saturation voltage; Pick and The larger value is used as the positive driving voltage for the fading process. .

[0015] Another technical solution of the present invention is: a method for preparing the multi-ion synergistic electrochromic film structure, the method comprising the following steps: S1. Substrate pretreatment: Select a flexible transparent polyimide substrate. The flexible transparent polyimide substrate is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence, and then activated by oxygen plasma. S2. Preparation of the first electrode layer: A transparent conductive oxide film, namely the first electrode layer, is prepared on a pretreated polyimide flexible transparent substrate using radio frequency magnetron sputtering. S3. Ion Storage and Catalytic Layer Preparation: Porous nanofilms were prepared using reactive magnetron sputtering. After preparation, Li was pre-embedded into the pores of the film using a constant current electrochemical embedding process. + and Na + ; S4. Preparation of solid-state mixed ion electrolyte layer: A polymer solid electrolyte matrix was prepared by solution spin coating process, and NASICON-type fast ion conductor nanoclusters were doped into the solid electrolyte matrix; S5. Preparation of the main electrochromic layer: A vertically grown array of WO3 nanorods was prepared on the surface of a solid mixed ionic electrolyte layer using a hydrothermal synthesis method. S6. Preparation of the second electrode layer: A transparent conductive oxide film is prepared on the surface of the WO3 nanorod array using radio frequency magnetron sputtering to form a symmetrical electrode structure with the first electrode layer.

[0016] Another technical solution of the present invention is: a multi-ion synergistic electrochromic porthole for manned spacecraft, wherein the porthole is fabricated using the above-mentioned multi-ion synergistic electrochromic film structure, and the specific fabrication process is as follows: Encapsulating a multi-ion synergistic electrochromic film structure within a pair of SiO₂ X Standardized electrochromic sandwich prefabricated components are formed between flexible films; then, the standardized electrochromic sandwich prefabricated components are integrally laminated to the inner surface of non-load-bearing glass using optical-grade OCA adhesive to form a multi-ion synergistic electrochromic porthole.

[0017] The advantages of this invention compared to the prior art are: (1) A leapfrog improvement in dimming performance: The multi-ion synergistic electrochromic mechanism proposed in this invention breaks through the traditional single Li + The system's performance bottleneck, through Li + Achieving millisecond-level rapid dimming of visible light through Na + It achieves high-efficiency heat insulation in the near-infrared band within seconds, simultaneously meeting the dual requirements of wide spectrum, wide-range dimming and high-efficiency heat insulation in space scenarios; the visible light transmittance can be as low as 10%, and the near-infrared band blocking rate can be as high as 92%, with a response speed that is more than an order of magnitude faster than traditional systems.

[0018] (2) Significantly enhanced adaptability and reliability to space environment: Through standardized prefabricated component packaging design and ALD full-encapsulation barrier technology, this invention effectively resists the erosion of electrochromic film system by the extreme space environment, greatly improving the cycle stability and on-orbit service life of the film system, with the electrochromic cycle count reaching 10. 6More than once, it fully meets the requirements of long life and high reliability for manned spacecraft. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the layered structure of the multi-ion synergistic electrochromic film described in an embodiment of the present invention; In the figure: 1 represents the first electrode layer, 2 represents the ion storage and catalysis layer, 3 represents the solid mixed ion electrolyte layer, 4 represents the main electrochromic layer, and 5 represents the second electrode layer. Detailed Implementation

[0020] The present invention will be further described below with reference to the embodiments.

[0021] This invention abandons the traditional single-ion driven electrochromic system and designs a multi-ion synergistic electrochromic film structure for manned spacecraft, along with its preparation method. It also describes a porthole fabricated based on this multi-ion synergistic electrochromic film structure. The multi-ion synergistic electrochromic film structure is an all-solid-state sandwich structure composite film system. Through the synergistic effect of two active alkali metal ions with different radii, it achieves wide-spectrum, fast-response dimming and heat insulation performance. The invention will be described in detail below with reference to embodiments: 1. Multi-ion synergistic electrochromic film structure like Figure 1 As shown, in a specific embodiment of the present invention, the multi-ion synergistic electrochromic film layer structure is provided with the following functional layers stacked sequentially from the inner glass substrate of the porthole outward: (1) First electrode layer 1: ITO, AZO and other transparent conductive oxide thin films with high light transmittance and high conductivity are used as the cathode driving electrode of the film system. The film thickness is controlled at 200-400nm and the sheet resistance is ≤15Ω / m. 2 Surface resistivity uniformity ≤ ±5%, visible light transmittance ≥ 85%; (2) Ion storage and catalytic layer 2: A porous nanofilm prepared using V2O5-TiO2 composite metal oxide, the film is rich in interconnected nanopore structures with a porosity ≥30%, and two active ions, Li, are pre-embedded in the pores. + and Na + This layer has dual functions of ion storage and electrochemical reaction catalysis. It completes the reversible insertion and extraction of ions during the electrochromic cycle, while balancing the charge of the film system and improving the cycle stability. The molar ratio of V2O5 to TiO2 is (6-8):(2-4), and the film thickness is controlled at 300-500nm. (3) Solid-state mixed ionic electrolyte layer 3: This is the core functional layer of the present invention. It adopts a polymer-based solid electrolyte matrix, in which NASICON-type fast ion conductor nanoclusters are uniformly dispersed. The solid electrolyte matrix can realize Li+ The rapid conduction of NASICON-type fast ion conductor nanoclusters possesses the ability to conduct Na+. + Selective conduction capability, Na + The ionic radius is greater than that of Li + This layer possesses high ionic conductivity, a wide electrochemical window, and excellent space environment stability, enabling the simultaneous realization of Li + and Na + Controllable, hierarchical transmission; In this embodiment, the core parameters of the solid-state hybrid ion electrolyte layer are: a PEO-based polymer solid electrolyte matrix and a NASICON-type Na3Zr2Si2PO4 electrolyte. 12 The fast ion conductor nanoclusters are doped with 8-15 wt%, with a nanocluster size controlled at 50-100 nm, and the solid-state mixed ion electrolyte layer has a thickness of 1-3 μm; Li at 25 °C + Electrical conductivity ≥1×10 -4 S / cm, Na + Electrical conductivity ≥ 5 × 10 -5 S / cm, electrochemical window ≥4V; (4) Main electrochromic layer 4: Using a vertically grown WO3 nanorod array structure, the specific surface area is stably controlled in the range of 45~60 m² / g by adjusting the diameter, length, spacing and porosity of the nanorods, providing abundant active sites and transport channels for ion insertion / extraction; at the same time, the pore structure between the nanorods can effectively alleviate the lattice stress caused by large-size ion insertion, and avoid film cracking and performance degradation. In this embodiment, the core parameters of the layer are: the diameter of the nanorods is 40-100nm, the length is 0.8-1.2μm, the array porosity is ≥40%, and the film thickness is controlled at 800-1200nm. (5) Second electrode layer 5: A transparent conductive oxide thin film identical to the first electrode layer is used as the anode driving electrode of the film system, forming a symmetrical electrode structure with the first electrode layer. The film thickness is controlled at 200-400 nm, and the sheet resistance is ≤15 Ω / m. 2 Surface resistivity uniformity ≤ ±5%, visible light transmittance ≥ 85%.

[0022] 2. Multi-ion cooperative working mechanism and hierarchical driving control strategy This invention achieves the stepped and controllable embedding of two active ions through differentiated ionic radii, migration rates, and selective conduction channels, simultaneously meeting the dual requirements of fast response anti-glare and deep thermal insulation. This allows the electrochromic color-changing process of the multi-ion synergistic electrochromic film structure to include a coloring process and a fading process. The coloring process includes a first-order fast response stage and a second-order deep coloring stage, realizing the Li... + First embedding, Na +Post-embedded hierarchical collaborative control.

[0023] The core mechanism is as follows: (1) Coloring process First-order fast response stage: When a negative driving voltage is applied to the multi-ion synergistic electrochromic film structure, i.e., the first electrode layer is connected to the positive terminal of the power supply and the second electrode layer is connected to the negative terminal of the power supply, Li, with its small ion radius and fast migration rate, will respond quickly. + First, the ion storage and catalytic layer is extracted and rapidly injected into the WO3 lattice of the main electrochromic layer through a solid mixed ion electrolyte layer, triggering the electrochromic reaction of WO3 and achieving rapid initial coloring in milliseconds (≤300ms). This completes the adjustment of transmittance in the visible light band, with a minimum visible light transmittance of 10%, instantly addressing the glare risk of sudden strong light in space. In this embodiment, the initial value of the negative driving voltage in the coloring process is -0.4V.

[0024] Second-order deep coloring stage: As the negative driving voltage is continuously applied (in this embodiment, the voltage is increased to -0.7V for 1-5s), Na+ ions with large ionic radii and slow migration rates... + Na is gradually injected into the WO3 lattice of the main electrochromic layer through the selectively conductive channels of NASICON-type fast ion conductor nanoclusters; + The embedding is used to shield the free electron plasma oscillation of WO3 material, enhance the absorption and reflection capabilities of the near-infrared band, and achieve second-level deep coloring on the basis of preliminary coloring. The near-infrared band blocking rate can reach up to 92%, reducing the heat load input in the cabin from the source and achieving efficient heat insulation. (2) Fading process When a positive driving voltage is applied to the multi-ion synergistic electrochromic film structure, i.e., the first electrode layer is connected to the negative terminal of the power supply and the second electrode layer is connected to the positive terminal of the power supply, Na + With Li + The cells can be reversibly de-intercalated from the main electrochromic layer and re-intercalated into the ion storage and catalytic layer. The multi-ion synergistic electrochromic film structure completes the fading within 2 seconds and returns to a high transmittance state. In this embodiment, the forward driving voltage is +0.15V to +0.5V.

[0025] With its all-solid-state film system's ion retention capability, the multi-ion synergistic electrochromic film structure possesses a static retention zero-power characteristic. That is, when the multi-ion synergistic electrochromic film structure reaches the target coloring / fading state, removing the negative / positive driving voltage can stably maintain the current optical state for more than 24 hours without continuous power supply, achieving extremely low on-orbit operation power consumption.

[0026] 3. Pressure-controlled properties of multi-ion synergistic electrochromic film structure In order to precisely adjust the visible light transmittance and near-infrared band blocking rate, it is necessary to calibrate the multi-ion synergistic electrochromic film structure to obtain the relationship between visible light transmittance and coloring voltage, near-infrared blocking rate and coloring voltage, visible light transmittance and fading voltage, and near-infrared blocking rate and fading voltage.

[0027] In a specific embodiment of the present invention, a polynomial fitting method is used to construct and solve the visible light transmittance-coloring voltage function, the near-infrared blocking rate-coloring voltage function, the near-infrared blocking rate-visible light transmittance function, the near-infrared blocking rate-fading voltage function, and the visible light transmittance-fading voltage function. Then, according to the definition of inverse functions, the coloring voltage-visible light transmittance function, the coloring voltage-near-infrared blocking rate function, the visible light transmittance-near-infrared blocking rate function, the fading voltage-near-infrared blocking rate function, and the fading voltage-visible light transmittance function are obtained. Specifically, as follows: 1) Visible light transmittance - coloring voltage function , Visible light transmittance-coloring voltage function Indicates the visible light transmittance of the electrochromic film layer. With Li + Coloring voltage The mapping relationship is such that the function is a monotonically decreasing function. Indicates that Li is driven separately + The coloring voltage, with a value range of Li + Embedded threshold voltage, with a value of 0.4V; Li + Saturation embedding voltage, taken as 0.9V. Visible light transmittance. The range of values ​​is express The highest light transmittance at that time was 85%. express The minimum transmittance at that time is set to 10%.

[0028] 2) Coloring voltage-visible light transmittance function Coloring voltage-visible light transmittance function It is a function of visible light transmittance and coloring voltage. The inverse function of the function is monotonically decreasing, and its analytical expression is shown below. 3) Near-infrared blocking rate - coloring voltage function , Near-infrared blocking rate - coloring voltage function Indicates the near-infrared blocking efficiency of the electrochromic film layer with Na + Coloring voltage The mapping relationship is such that the function is a monotonically increasing function. Indicates that Na is driven separately. + The coloring voltage, with a value range of ; Na represents + Embedded threshold voltage, with a value of 0.7V; Na represents + Saturation embedding voltage, taken as 1.4V. Near-infrared blocking rate. The range of values ​​is , express The minimum near-infrared blocking rate is set at 20%. express The highest near-infrared blocking rate was 92%.

[0029] 4) Coloring voltage-near-infrared blocking rate function Coloring voltage-near-infrared blocking rate function It is a function of near-infrared blocking rate and coloring voltage. The inverse function of the function is monotonically increasing, and its analytical expression is shown below. 5) Near-infrared blocking rate - visible light transmittance function Li + and Na + Driven by the same voltage, Li + First embedding, Na + Post-embedding. Only when Li + Coloring voltage greater than Li Shi + Activate embedded control of visible light transmittance , only if Na + Coloring voltage greater than And Li + After pre-embedding is completed, Na + Activate embedded modulation of near-infrared blocking rate .

[0030] Visible light transmittance As the color voltage increases, the near-infrared blocking rate decreases strictly and monotonically. The color voltage increases strictly monotonically with increasing color voltage. Therefore, by using the color voltage as an intermediate variable, the near-infrared blocking rate can be obtained. With visible light transmittance The functional relationship is shown in the following formula: Near-infrared blocking rate - Visible light transmittance function. It is a monotonically decreasing function.

[0031] 6) Visible light transmittance - near-infrared blocking rate function Visible light transmittance - near-infrared blocking rate function It is a function of near-infrared blocking rate and visible light transmittance. The inverse function of the function, which is monotonically decreasing, is shown in the following equation. 7) Near-infrared blocking rate - fading voltage function The calculation logic for the fading process is the same as that for the coloring process, only the voltage polarity is reversed; the fading process is driven by a positive DC voltage. Under the action of the positive driving voltage, Na+ ions with larger ionic radii... + The insertion / extraction barrier is lower, leading to earlier insertion / extraction and a corresponding decrease in near-infrared blocking efficiency; Li has a smaller ionic radius. + Post-deintercalation results in increased visible light transmittance. Near-infrared blocking rate decreases strictly monotonically with increasing fading voltage; the near-infrared blocking rate versus fading voltage function... The analytical expression is shown below.

[0032] Near-infrared blocking rate-fading voltage function Indicates the near-infrared blocking efficiency of the electrochromic film layer with Na + Fading voltage The mapping relationship, Indicates that Na is driven separately. + The fading voltage, with a value range of [value missing]. ; Na represents + The de-intercalation threshold voltage is set to 0.15V. Na represents + The complete deintercalation saturation voltage is set to 0.3V. Near-infrared blocking rate. The value range is [92%, 20%].

[0033] 8) Fading voltage-near-infrared blocking rate function Fading voltage-near-infrared blocking rate function It is a function of near-infrared blocking rate and fading voltage. The inverse function of is shown in the following expression.

[0034] 9) Visible light transmittance - fading voltage function Visible light transmittance-fading voltage function Indicates the visible light transmittance of the electrochromic film layer. With Li + Fading voltage The mapping relationship is such that the function is a monotonically increasing function. Indicates that Li is driven separately + The fading voltage, with a value range of [value missing]. ; Li + The de-intercalation threshold voltage is set to 0.2V. Li + The complete deintercalation saturation voltage is set to 0.5V. Visible light transmittance. The value range is [10%, 85%].

[0035] 10) Fading voltage-visible light transmittance function Fading voltage-visible light transmittance function It is a function of visible light transmittance and fading voltage. The inverse function of is shown in the following expression.

[0036] 4. Setting the negative drive voltage during the coloring process Negative driving voltage during the coloring process For unipolar DC voltage, to realize Li + First embedding, Na + The embedded hierarchical collaborative control meets the design requirements of millisecond-level visible light dimming and second-level near-infrared heat insulation, and is divided into pre-calibration, Li + Colored voltage calculation, Na + The process involves four steps: calculating the coloring voltage and the negative driving voltage during the coloring process.

[0037] (1) Pre-calibration Calibration of the coloring voltage-visible transmittance function of multi-ion synergistic electrochromic film structure Coloring voltage-near-infrared blocking rate function ; (2) Calculate the individual driving Li + Coloring voltage (Visible light dimming) Based on the target value of visible light transmittance Coloring voltage-visible light transmittance function Combined with the incident angle correction factor get Independently drive Li + Coloring voltage The expression is as follows: , The expression is as follows: In the formula Indicates the angle of incidence of sunlight. ,when At that time, realize Li + Millisecond-level embedding rapidly reduces visible light transmittance, fundamentally solving the glare problem and meeting the "zero-delay" dimming requirement.

[0038] (3) Calculate the individual driving Na + Coloring voltage (Near-infrared heat insulation) Based on the target value of near-infrared blocking rate Coloring voltage-near-infrared blocking rate function Combined with the ion-coordinated voltage coupling coefficient ,get Ensure Na + In Li + After startup, it quickly follows up with the embedding, achieving deep thermal insulation in seconds, as shown in the following formula. In the formula ,and (Guarantee Na) + In Li + (Pre-embedded startup); The value is 0.9, representing that when Li + After embedding, Na + The embedding barrier is lowered, eliminating the need for separate driving of Na. + Voltage.

[0039] (4) Calculate the negative driving voltage of the coloring process. Li + / Na + Driven by the same voltage, therefore and To merge, take and The larger value in the range is used as the negative driving voltage for the coloring process. This ensures that both types of ions can be embedded according to the target requirements, achieving synergistic regulation of visible light and near-infrared light, as shown in the following formula. In the formula ,when At that time, Li + First to embed and achieve visible light dimming; when When, Na + It can be embedded to achieve near-infrared thermal insulation; a single voltage can achieve hierarchical coordination, simplifying the design of spaceborne drive circuits and meeting the needs of engineering implementation.

[0040] 5. Setting the forward drive voltage during the fading process The fading process of electrochromic films (Li + / Na + (De-intercalation and restoration of high transmittance) is driven by a positive DC voltage. The calculation logic is consistent with the coloring process, only the voltage polarity is reversed, to achieve Na… + First, embedding, Li + The sequential fading process following insertion and extraction ensures smoothness and optical consistency during the fading process, and is divided into pre-calibration and Na... + Calculation of fading voltage, Li + Four steps to calculate fading voltage and the forward driving voltage of the fading process: (1) Pre-calibration Calibration of the fading voltage-near-infrared blocking rate function of multi-ion synergistic electrochromic film structure and fading voltage-visible light transmittance function ; (2) Calculate the individual driving Na + fading voltage Based on the target value of near-infrared blocking rate and fading voltage-near-infrared blocking rate function To obtain a separate driving Na + fading voltage As shown in the following formula In the formula, .

[0041] (3) Calculate the independent drive Li + fading voltage Based on the target value of visible light transmittance and fading voltage-visible light transmittance function ,get As shown in the following formula In the formula, .

[0042] (4) Calculate the forward driving voltage during the fading process. Li + / Na + Driven by the same driving voltage, therefore and To merge, take and The larger value in the range is used as the positive driving voltage for the fading process. To ensure that both types of ions can be inserted and extracted according to the target requirements, synergistic modulation using visible light and near-infrared light is achieved, as shown in the following formula: In the formula ,when When, Na + First to disembed; when At that time, Li + Initiate de-embedding; single-channel voltage can achieve graded coordination, simplifying the design of spaceborne drive circuits and meeting the requirements for engineering implementation.

[0043] 6. Preparation method of multi-ion synergistic electrochromic film structure In this embodiment, a multi-ion synergistic electrochromic film structure was prepared using a combined magnetron sputtering and atomic layer deposition (ALD) process in a Class 100 cleanroom environment. The specific process is as follows: (1) Substrate pretreatment: A flexible transparent polyimide (PI) substrate with a thickness of 50 μm was selected. The substrate was ultrasonically cleaned with anhydrous ethanol and deionized water in sequence, and then activated by oxygen plasma to improve the adhesion of the film layer. (2) Preparation of the first electrode layer: A transparent conductive oxide film (ITO transparent conductive film) with a thickness of 300 nm was prepared on the pretreated flexible substrate using radio frequency magnetron sputtering, which is the first electrode layer. The process parameters of the first electrode layer are: sputtering power 100 W, argon flow rate 20 sccm, working pressure 0.5 Pa, and substrate temperature room temperature. After preparation, the sheet resistance of the transparent conductive oxide film was controlled at 10 Ω / m. 2 Within a certain range, the surface resistivity uniformity is controlled within 5%, and the visible light transmittance is ≥85%. (3) Ion storage and catalyst layer preparation: A V2O5-TiO2 composite porous nanofilm with a thickness of 400 nm was prepared by reactive magnetron sputtering, wherein the molar ratio of V2O5 to TiO2 was 7:3 and the porosity of the film was ≥30%; after preparation, Li was pre-embedded in the pores of the film using a constant current electrochemical embedding process. + and Na +In a specific embodiment of the present invention, Li is embedded... + The quantity is controlled at 50% of the theoretical saturation capacity; (4) Preparation of solid-state mixed ionic electrolyte layer: A PEO-based polymer solid electrolyte with a thickness of 2 μm was prepared by solution spin coating process. The solid electrolyte matrix was doped with 10 wt% NASICON-type Na3Zr2Si2PO4. 12 Fast ion conductor nanoclusters, with nanocluster particle size controlled at 50-100 nm; Li solid mixed ion electrolyte layer at 25 °C + Electrical conductivity ≥1×10 -4 S / cm, Na + Electrical conductivity ≥ 5 × 10 -5 S / cm; (5) Preparation of the main electrochromic layer: A vertically grown WO3 nanorod array was prepared on the surface of a solid mixed ionic electrolyte layer by a hydrothermal synthesis method. The nanorods had a diameter of 50-80 nm, a length of 1 μm, and an array porosity of ≥40%. (6) Fabrication of the second electrode layer: A 300 nm thick transparent conductive oxide film (ITO transparent conductive film) was fabricated on the surface of the WO3 nanorod array using radio frequency magnetron sputtering. This film serves as the anode driving electrode, forming a symmetrical electrode structure with the first electrode layer. The process parameters were: sputtering power 100 W, argon flow rate 20 sccm, working pressure 0.5 Pa, and substrate temperature room temperature. After fabrication, the sheet resistance of the film was controlled at 10 Ω / m. 2 Within 5%, the surface resistivity uniformity is controlled within 5%, and the visible light transmittance is ≥85%.

[0044] 7. Preparation method of electrochromic portholes for manned spacecraft This embodiment applies the above-mentioned multi-ion synergistic electrochromic film structure to a multi-ion synergistic electrochromic porthole for a near-Earth orbit manned spacecraft. The specific preparation process is as follows: Step S1: Preparation of multi-ion synergistic electrochromic sandwich preform Using atomic layer deposition (ALD) technology, the complete multi-ion synergistic electrochromic film system is fully encapsulated in a pair of high-barrier flexible films to form a standardized "electrochromic sandwich preform". In this embodiment, the ALD process is used to deposit Al2O3 barrier layers with a thickness of 20 nm on the upper and lower surfaces of the complete film system, and then the entire film system is encapsulated in a pair of SiO2 layers with a thickness of 25 μm. X (In this embodiment of the invention, the X value is controlled between 1.5 and 1.8) A complete electrochromic sandwich preform is formed between high-barrier flexible films; after encapsulation, the water and oxygen permeability of the preform is ≤1×10⁻⁶. -6 g / (m²·24h), meeting the requirements for use in space environments.

[0045] Step S2: Assembly of prefabricated components and porthole structure (1) Select non-load-bearing fused silica glass for the inner side of the manned spacecraft window, and perform cleaning, hydroxylation and plasma activation treatment on the inner surface of the glass in sequence; (2) Using optical grade OCA adhesive with a thickness of 100μm, the electrochromic sandwich preform prepared in step S1 is laminated onto the inner surface of the inner glass of the port window. The lamination process adopts vacuum hot pressing process, with a temperature of 60℃, a pressure of 0.5MPa, and a holding pressure of 30min to completely eliminate air bubbles and ensure the bonding strength and optical consistency. (3) Connect the lead-out ends of the first electrode layer and the second electrode layer of the prefabricated component to the corresponding partition drive electrodes integrated inside the window frame; The prefabricated components are integrally laminated to the inner surface of the non-load-bearing glass on the inside of the window using optical-grade OCA adhesive, which prevents the membrane system from being directly exposed to the space environment. This effectively resists the corrosion of extreme conditions such as atomic oxygen, strong cosmic rays, and high and low temperature cycles, and significantly improves the on-orbit service life and cycle stability of the membrane system.

[0046] Compared with the prior art, the present invention has the following outstanding substantive features and significant beneficial effects: (1) A leapfrog improvement in dimming performance: The multi-ion synergistic electrochromic mechanism proposed in this invention breaks through the traditional single Li + The system's performance bottleneck, through Li + Achieving millisecond-level rapid dimming of visible light through Na + It achieves high-efficiency heat insulation in the near-infrared band within seconds, simultaneously meeting the dual requirements of wide spectrum, wide-range dimming and high-efficiency heat insulation in space scenarios; the visible light transmittance can be as low as 10%, and the near-infrared band blocking rate can be as high as 92%, with a response speed that is more than an order of magnitude faster than traditional systems.

[0047] (2) Significantly enhanced adaptability and reliability to space environment: Through standardized prefabricated component packaging design and ALD full-encapsulation barrier technology, this invention effectively resists the erosion of electrochromic film system by the extreme space environment, greatly improving the cycle stability and on-orbit service life of the film system, with the electrochromic cycle count reaching 10. 6 More than once, it fully meets the requirements of long life and high reliability for manned spacecraft.

[0048] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make possible changes and modifications to the technical solutions of the present invention by utilizing the methods and techniques disclosed above without departing from the spirit and scope of the present invention. Therefore, any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention shall fall within the protection scope of the technical solutions of the present invention.

Claims

1. A multi-ion synergistic electrochromic film structure for manned spacecraft, characterized in that... It includes a first electrode layer, an ion storage and catalytic layer, a solid-state mixed ion electrolyte layer, a main electrochromic layer, and a second electrode layer; wherein: The first electrode layer and the second electrode layer are transparent conductive oxide thin films. The first electrode layer is used as a cathode driving electrode, and the second electrode layer is used as an anode driving electrode. The ion storage and catalytic layer is a porous nanofilm containing interconnected nanopores within which two active ions, Li, are pre-embedded. + and Na + ; A solid-state hybrid ionic electrolyte layer comprises a polymer-based solid electrolyte matrix, within which NASICON-type fast ion conductor nanoclusters are dispersed; the solid electrolyte matrix is ​​used to realize Li + The NASICON-type fast ion conductor nanoclusters possess the ability to conduct Na+. + Selective conduction capability; The main electrochromic layer is a vertically grown WO3 nanorod array structure.

2. The multi-ion synergistic electrochromic film structure for manned spacecraft according to claim 1, characterized in that, The porosity of the ion storage and catalyst layer is ≥30%.

3. The multi-ion synergistic electrochromic film structure for manned spacecraft according to claim 1, characterized in that, In the solid-state hybrid ion electrolyte layer, the polymer-based solid electrolyte matrix is ​​a PEO-based polymer solid electrolyte, the NASICON-type fast ion conductor nanoclusters are doped with an amount of 8-15wt%, the nanocluster particle size is controlled at 50-100nm, and the thickness of the solid-state hybrid ion electrolyte layer is 1-3μm.

4. The multi-ion synergistic electrochromic film structure for manned spacecraft according to claim 1, characterized in that, In the main electrochromic layer, the porosity of the WO3 nanorod array structure is ≥40%, and the specific surface area is controlled in the range of 45~60m² / g.

5. The multi-ion synergistic electrochromic film structure for manned spacecraft according to claim 1, characterized in that, The electrochromic lighting process of the multi-ion synergistic electrochromic film structure includes a coloring process and a fading process. The coloring process includes a first-order fast response stage and a second-order deep coloring stage, realizing Li + First embedding, Na + Post-embedded hierarchical collaborative control, wherein: First-order fast response stage: Applying a negative driving voltage to the multi-ion synergistic electrochromic film structure, Li ions with small ionic radii and fast migration rates... + First, the ion storage and catalytic layer is extracted and inserted into the WO3 lattice of the main electrochromic layer through the solid mixed ion electrolyte layer, triggering the electrochromic reaction of WO3 and achieving millisecond-level initial coloring. Second-order depth coloring stage: As the negative driving voltage is continuously applied, Na+ ions with large ionic radii and slow migration rates... + Through the selectively conductive channels of NASICON-type fast ion conductor nanoclusters, they are gradually embedded into the WO3 lattice of the main electrochromic layer, achieving second-level deep coloring on the basis of preliminary coloring.

6. The multi-ion synergistic electrochromic film structure for manned spacecraft according to claim 5, characterized in that, The negative driving voltage for the coloring process is determined by the following method: Calibration of the coloring voltage-visible transmittance function of multi-ion synergistic electrochromic film structure Coloring voltage-near-infrared blocking rate function ; Based on the target value of visible light transmittance Coloring voltage-visible light transmittance function Combined with the incident angle correction factor To obtain a separate driver for Li + The coloring voltage, denoted as ; In the formula Li + Embedded threshold voltage, Li + Saturation embedding voltage; Based on the target value of near-infrared blocking rate Coloring voltage-near-infrared blocking rate function Combined with the ion-coordinated voltage coupling coefficient To obtain a separate driving Na + The coloring voltage, denoted as Ensure Na + In Li + Embedded functionality will be implemented after startup; In the formula Na represents + Embedded threshold voltage, Na represents + Saturation embedding voltage; Pick and The larger value in the range is used as the negative driving voltage for the coloring process. .

7. The multi-ion synergistic electrochromic film structure for manned spacecraft according to claim 5, characterized in that, The fading process is as follows: when a positive driving voltage is applied to the multi-ion synergistic electrochromic film structure, Na... + and Li + The cells were successively de-intercalated from the main electrochromic layer and re-intercalated into the ion storage and catalytic layer, and the multi-ion synergistic electrochromic film structure completed the fading process.

8. The multi-ion synergistic electrochromic film structure for manned spacecraft according to claim 7, characterized in that, The forward driving voltage for the fading process is determined by the following method: Calibration of the fading voltage-near-infrared blocking rate function of multi-ion synergistic electrochromic film structure and fading voltage-visible light transmittance function ; Based on the target value of near-infrared blocking rate and fading voltage-near-infrared blocking rate function To obtain a separate driving Na + fading voltage ; In the formula Na represents + De-intercalation threshold voltage Na represents + Complete de-intercalation saturation voltage; Based on the target value of visible light transmittance and fading voltage-visible light transmittance function To obtain a separate driver for Li + fading voltage ; In the formula , Li + De-intercalation threshold voltage Li + Complete de-intercalation saturation voltage; Pick and The larger value is used as the positive driving voltage for the fading process. .

9. The method for preparing the multi-ion synergistic electrochromic film structure for manned spacecraft as described in claim 1, characterized in that... Includes the following steps: S1. Substrate pretreatment: Select a flexible transparent polyimide substrate. The flexible transparent polyimide substrate is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence, and then activated by oxygen plasma. S2. Preparation of the first electrode layer: A transparent conductive oxide film, namely the first electrode layer, is prepared on a pretreated polyimide flexible transparent substrate using radio frequency magnetron sputtering. S3. Ion storage and catalytic layer preparation: Porous nanofilms were prepared using reactive magnetron sputtering. After preparation, Li was pre-embedded in the pores of the thin film using a constant current electrochemical intercalation process. + and Na + ; S4. Preparation of solid-state mixed ion electrolyte layer: A polymer solid electrolyte matrix was prepared by solution spin coating process, and NASICON-type fast ion conductor nanoclusters were doped into the solid electrolyte matrix; S5. Preparation of the main electrochromic layer: A vertically grown array of WO3 nanorods was prepared on the surface of a solid mixed ionic electrolyte layer using a hydrothermal synthesis method. S6. Preparation of the second electrode layer: A transparent conductive oxide film is prepared on the surface of the WO3 nanorod array using radio frequency magnetron sputtering to form a symmetrical electrode structure with the first electrode layer.

10. A multi-ion synergistic electrochromic porthole for manned spacecraft, characterized in that... The film is prepared using the multi-ion synergistic electrochromic film structure described in any one of claims 1 to 8, and the specific preparation process is as follows: The multi-ion synergistic electrochromic film structure according to any one of claims 1 to 8 is encapsulated in a pair of SiO₂ X Standardized electrochromic sandwich preforms are formed between flexible films; then, the standardized electrochromic sandwich preforms are integrally laminated to the inner surface of non-load-bearing glass using optical-grade OCA adhesive to form a multi-ion synergistic electrochromic porthole, with X values ​​ranging from 1.5 to 1.8.